A comprehensive literature review on, and the construction of a framework for, environmental legitimacy, accountability and proactivity - Alrazi B.; De Villiers C.; Van Staden C.J. (Elsevier Ltd, 2023)
Sustainable development; Accountability; ELAP framework; Environmental performance; Legitimacy; Pro activities; Environmental management